The Effect Of Job Placement And Employee Recruitment On Employee Performance - Budi Rismayadi; Wike Pertiwi; Mumun Maemunah (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — The purpose of this study was to determine the effect of recruitment and job placement on the performance of Karawang MSME employees.. Research method— The method used in this study is a quantitative verification method. The data collection technique used in this study used a questionnaire with a Likert scale. While the data analysis used was multiple linear regression analysis with SPSS 29 software.. Result— The results of this study indicate that there is a partial effect between employee recruitment and performance significantly of 0.000 <0.005 and a t-count value of 7.584> 2.011 and a partial effect between job placement and performance significantly of 0.000 <0.005 and a t-count value of 3.793> 2.011. Together, employee recruitment and job placement are proven to have a simultaneous significant effect on employee performance which shows a very significant effect of 0.000 <0.005 with an F-Count value of 186.501> 3.19. Based on the results of the determination coefficient, it was found that the employee recruitment and job placement variables had an influence of 88.8%, while the remaining 1.2% was explained by other unknown factors or variables that were not included in this regression analysis. Conclusion— the Employee Recruitment Variable (X1) has a positive and very significant influence on the Employee Performance variable (Y) in Karawang MSMEs. the Job Placement Variable (X2) has a positive influence on the employee performance variable (Y), which means that the job placement variable has an influence on employee performance at MSMEs Karawang. the Employee Recruitment Variable (X1) and Job Placement variable (X2) have a positive and significant influence on the Employee Performance variable (Y) in Karawang MSMEs.